Primary constitutional MLH1 epimutations: a focal epigenetic event. Issue 8 (16th October 2018) - Dámaso, Estela; Castillejo, Adela; Arias, María del Mar; Canet-Hermida, Julia; Navarro, Matilde; del Valle, Jesús; Campos, Olga; Fernández, Anna; Marín, Fátima; Turchetti, Daniela; García-Díaz, Juan de Dios; Lázaro, Conxi; et al.
Abstract Background ConstitutionalMLH1 epimutations are characterised by monoallelic methylation of theMLH1 promoter throughout normal tissues, accompanied by allele-specific silencing. The mechanism underlying primaryMLH1 epimutations is currently unknown. The aim of this study was to perform an in-depth characterisation of constitutionalMLH1 epimutations targeting the aberrantly methylated region aroundMLH1 and other genomic loci. Methods TwelveMLH1 epimutation carriers, 61 Lynch syndrome patients, and 41 healthy controls, were analysed by Infinium 450 K array. Targeted molecular techniques were used to characterise theMLH1 epimutation carriers and their inheritance pattern. Results No nucleotide or structural variants were identifiedin-cis on the epimutated allele in 10 carriers, in which inter-generational methylation erasure was demonstrated in two, suggesting primary type of epimutation. CNVs outside theMLH1 locus were found in two cases.EPM2AIP1-MLH1 CpG island was identified as the sole differentially methylated region inMLH1 epimutation carriers compared to controls. Conclusion Primary constitutionalMLH1 epimutations arise as a focal epigenetic event at theEPM2AIP1-MLH1 CpG island in the absence ofcis -acting genetic variants. Further molecular characterisation is needed to elucidate the mechanistic basis ofMLH1 epimutations and their heritability/reversibility.